Let f be a differentiable function on the real numbers satisfying, for all real numbers x , y ,
f ( x + y ) = f ( x ) + f ( y ) + x y
and h → 0 lim h f ( h ) = 3 . What is the value of f ( 1 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
On putting x=y=0,
f(0)=f(0)+f(0)
=> f(0)=0
f ' (x) = lim(h-->inf) [{f(x+h)-f(x)}/ {(x+h)- x}]
and
f(x+h)= f(x)+f(h)+xh (from given identity)
therefore,
f ' (x)= lim(h-->inf) {f(h)+xh}/h
= lim(h-->inf) f(h)/h + lim(h-->inf) xh/h
= 3+x
On integrating,
f(x)= (x^2)/2 + 3x + c
but f(0)=0
==> f(x)= (x^2)/2+3x
==>f(1)=7/2
Good approach, and keeping track of all the details.
Your solution can be improved by providing clearer guidelines about what you are trying to achieve.
Replacing x = y = 0 we get f ( 0 ) = 2 f ( 0 ) ⟹ f ( 0 ) = 0 . Thus lim h → 0 h f ( h ) = lim h → 0 h f ( 0 + h ) − f ( h ) = f ′ ( 0 ) . So f ′ ( 0 ) = 3 .
Now differentiate the functional equation with respect to x to get f ′ ( x + y ) = f ′ ( x ) + y . Evaluate at x = 0 to get f ′ ( y ) = 3 + y . Integrate with respect to y to get f ( y ) = 3 y + 2 y 2 + C . Because f ( 0 ) = 0 we know that C = 0 . The solution to the functional equation is thus f ( y ) = 3 y + 2 y 2 . And f ( 1 ) = 2 7 .
At first differentiate the function wrt x keeping y constant. Then put x in places of y and 0 in place of x. From this we get f '(x)=f '(0)+x. From putting x=y=0 in the parental eqn we get f(0)=0 rewriting f(h)=f(h+0)-f(0), we get from the limit that f '(0)=3. Hence we get fx as=x+3 and integrating and comparing withf0 we get fx.
Problem Loading...
Note Loading...
Set Loading...
f ( x + y ) f ( 0 ) ⟹ f ( 0 ) f ( x + h ) h f ( x + h ) − f ( x ) h → 0 lim h f ( x + h ) − f ( x ) f ′ ( x ) ⟹ f ( x ) f ( 0 ) ⟹ f ( x ) f ( x + y ) ⟹ f ( 1 ) = f ( x ) + f ( y ) + x y = 2 f ( 0 ) = 0 = f ( x ) + f ( h ) + x h = h f ( h ) + x = h → 0 lim h f ( h ) + x = 3 + x = 3 x + 2 x 2 + C = 0 = 3 x + 2 x 2 = 3 x + 2 x 2 + 3 y + 2 y 2 + x y = 3 + 2 1 = 2 7 Given; putting x = y = 0 Putting y = h Rearranging and dividing both sides by h Taking limit of h → 0 Given that h → 0 lim h f ( h ) = 3 where C is the constant of integration. ⟹ C = 0 And ⟹ f ( x + y ) = f ( x ) + f ( y ) + x y as given.